APPLICATION OF PLANT BASED EXTRACTS FOR THE CONTROL THE GREEN PITSCALE INSECT (ASTEROLICANIUM PHOENICIS RAO.) WITH YIELDENHANCEMENT ON DATE PALM - Eldoush, Khalid O. A. M.; Taha, Awad K.; Idris, Tag Elsir I. M.; A. Sidahmed, Omar A.; Musa, Fakhr Eldeen A.; Mardi, Hatim G. (Emirates Journal of Food and Agriculture, 2011)
A field study was carried out at Alghaba Agricultural Scheme, Northern State, Sudan, to investigate the effects of the powder of argel (Solenostemma argel Del. Hyne.) and usher (Calotropis procera Ait.) on adult females of the green pit scale insect (Asterolicanium phoenicis Rao.), in addition to their effects on date palm production. The powder of each plants was applied under three doses (100 g. powder/ tree as a soil dressing, 100 g. powder /10 Liter water/ tree for spraying and 100 g. powder as a soil dressing + 100 g. powder /10 Liter water for spraying/ tree). The synthetic insecticide Actara 25 W.G. Thimethoxam (Neonicotinoid) was used as a standard insecticide. All treatments of the study gave higher percentages of mortality of adult females compared to untreated control up to the 8th week after application. The mortality percentages of adult females ranged between 40 to 66% and 31 to 41% for argel and usher plants based extracts, respectively. According to the results of this study, argel and usher application in soil (100g. powder / tree) should be recommended as an effective treatment to control the green date palm pit scale insect. Also, the results showed that these plant ?based extracts have a positive effect on date palm yield.